Toxic Behavior Sebagai Komunikasi Virtual Pemain Game Online Mobile Legends: Bang Bang - Latif Ahmad Fauzan; Augustin Mustika Chairil; Ahimsa Adi Wibowo (JKOM, 2021)
Toxic Behavior Sebagai Komunikasi Virtual Pemain Game Online Mobile Legends: Bang Bang